IMPROVING TEACHER DISCIPLINE IN ATTENDANCE TEACHING IN THE CLASS THROUGH THE IMPLEMENTATION OF REWARD AND PUNISHMENT AT THE 017 TAMBUSAI STATE ELEMENTARY SCHOOL ROKAN HULU DISTRICT - Fatimah Fatimah (STKIP Rokania Pasir Pangaraian, 2021)
This study aims to improve teacher discipline in teaching attendance in class through the application of Reward and Punishment. This research was carried out in two cycles, because from the results of research and data analysis, it turned out that in the second cycle, teacher discipline in class attendance in the teaching and learning process increased and met the predetermined indicators of 75%. From the results of this study, it can be concluded that to improve teacher discipline in class attendance in teaching and learning activities can be done by applying Reward and Punishment to teachers.